The Influence of Change Management, Organizational Commitment, and Supervision on the Integrity of Police Members in the Gorontalo Regional Police Department - Paramata, Mohamad Rolli; Yakup, Yakup; Usu, Idrus; Runtukahu, Berty Hanry (Indonesian Journal Publisher, 2024)
This research aims to analyze the influence of change management, human resource quality, organizational commitment, and supervision on the integrity of police members in the Gorontalo Regional Police Department. The research population consists of 75 respondents using an incidental method. The analytical technique used to address the research problem and test hypotheses is multiple regression analysis with the assistance of Statistical Product Service Solution (SPSS) software. The findings of this research are as follows: (1) change management has a positive and significant influence on the integrity of police members, (2) organizational commitment has a positive and significant influence on the integrity of police members, and (3) supervision has a positive and significant influence on the integrity of police members